Illicit methylphenidate use among Iranian medical students: prevalence and knowledge - Afshin Habibzadeh Mahasti Alizadeh Ayoub Malek; et al (Dove Medical Press, 2011)
Afshin Habibzadeh1 Mahasti Alizadeh2 Ayoub Malek3 Leili Maghbooli1 Mohammadali M Shoja4 Kamyar Ghabili41Students' Research Committee, 2Department of Community Medicine, 3Department of Psychiatry, 4Tuberculosis and Lung Disease Research Center, Tabriz University of Medical Sciences, Tabriz, IranBackground: Methylphenidate, a medication prescribed for individuals suffering from attention-deficit/hyperactivity disorder, is increasingly being misused by students.Objective: The aims of this study were to evaluate the frequency of methylphenidate use among a group of Iranian medical students and to assess their knowledge of methylphenidate.Methods: Anonymous, self-administered questionnaires were completed by all medical students entering the university between 2000 and 2007.Results: Methylphenidate users’ mean knowledge score was higher than that of nonusers (15.83 ± 3.14 vs 13.66 ± 3.10, P = 0.008). Age, gender, and school year were positively correlated with knowledge score (P < 0.05). Data analysis demonstrated that 27 participants (8.7%) had taken methylphenidate at least once in their lifetime. The respondents believed that the most common motive for methylphenidate use among youths was that it aided concentration and therefore ability to study.Conclusion: This study indicates a relatively low level of knowledge about methylphenidate among Iranian medical students. More educational programs regarding the use of methylphenidate are required and should be focused on the student suppliers, clinicians, pharmacists, and medical students.Keywords: methylphenidate, medical student, prevalence, Iran